The Effect of Text Authenticity on the Performance of Iranian EFL Students in a C-Test - Cheng, Karen Kow Yip; BiglarBaygi, Amir; Solaymani, Mesod (Research in Language, 2009)
As part of growing efforts to understand factors affecting c-test this study aims to investigate the effect of text authenticity on the performance of Iranian EFL students in a C-Test. The C-Test is an integrative testing instrument that measures overall language competence, very much like the cloze test. In this study the rule of two has been applied: “the second half of every second word has been deleted, beginning with the second word of the second sentence; the first and last sentences are left intact” (Katona and Dornyei 1993: 35). The research involves 60 college students in their third year, majoring in English Literature at Ershad-Damavand College. This group were randomly selected applying multi-stage sampling. Since the present study intended to investigate the role of two different formats, i.e. authentic and inauthentic texts (text translated from Persian into English), two different tailored C-Tests were made to measure and compare the performances of the participants. Two C-Tests, one with Authentic Text and the other, with Inauthentic Text were administered to this homogenized group comprising 30 subjects. The findings of this study suggest that authenticity has an effect on the performance of learners in c-tests and we should control this variable while devising a c-test.